Reduced Density of Calbindin Immunoreactive GABAergic Neurons in the Occipital Cortex in Major Depression: Relevance to Neuroimaging Studies - Maciag, Dorota; Hughes, Jonathan; O'Dwyer, Gillian; Pride, Yilianys; Stockmeier, Craig A.; Sanacora, Gerard; Rajkowska, Grazyna (Biological psychiatry (1969), 2010)
Several lines of evidence suggest dysfunction of the γ-aminobutyric acid (GABA)ergic system in major depressive disorder. Neuroimaging studies report reduced levels of GABA in the dorsolateral prefrontal and occipital cortex of depressed patients. Our previous postmortem study revealed a reduction in the density and size of calbindin-immunoreactive (CB-IR) GABAergic neurons in the prefrontal cortex in major depressive disorder. The goal of this study was to test whether the changes in CB-IR neurons can also be detected in the occipital cortex, where neuroimaging studies report a prominent GABA decrease. A three-dimensional cell counting probe was used to assess the cell-packing density and size of CB-IR neurons in layer II of the occipital cortex in 10 major depressive disorder subjects and 10 psychiatrically healthy control subjects. The density of CB-IR neurons was significantly decreased by 28% in major depressive disorder subjects compared with the control group. The size of CB-IR neurons was unchanged in major depressive disorder subjects when compared with control subjects. The reduction in the density of CB-IR GABAergic neurons in the occipital cortex in depression is similar to that observed previously in the prefrontal cortex. Deficit in cortical GABAergic interneurons may contribute to the low GABA levels detected in neuroimaging studies in major depressive disorder patients.